Retraction Note to: Workplace bullying and its preventive measures and productivity among emergency department nurses - Suhair Hussni Al-Ghabeesh; Haya Qattom (BMC, 2019)
The Publisher has retracted this article [1] because it was published in this journal in error. This article is republished in BMC Health Services Research [2].